USAHA GURU BK UNTUK MEMBANTU MEMENUHI KEBUTUHAN SOSIAL REMAJA DALAM BELAJAR DI SMP N 2 PULAU PUNJUNG KABUPATEN DHARMASRAYA - Latif, Fauziah; Ibrahim, Indra; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
The researcher found phenomenon there are students that do not able to respond in learning, the student have not ability work with team, the students do not care with group activity, the students are not own confidence to build new connection and students can not control their negative emotion. The problem in this research is the counsellor effort help to fill teenagers social necessary in learning. This research purpose to description: 1) the counsellor effort help to fill teenagers necessary to know in learning, 2) the counsellor effort help to fill teenagers necessary to make group in learning, 3) the counsellor effort help to fill teenagers necessary that have good habit in learning, 4) the counsellor help to fill teenagers self actualization necessary in learning. Genre of this research is descriptive research that fills to imagine about simple situation. The population in this research are students in SMP N 2 Pulau Punjung Dharmasraya regency that number 484 students. The sample in this research use multistage sampling. The numbers are 83 students. Source data in this research are primary data and secondary data. The instrument is used in this research is inquiry. Whereas to data analysis is used percentage teaches. The result of this research found that imagine about counsellor help to fill social teenagers necessary in learning be at good category. Based of research result, the result give suggestion to counsellor can in crease effort that connected with fill teenager necessary, then to students in order to have understanding ability about fill by their self.Â